Geai Bleu - CONCEIÇÃO, Edicledisson Santana da; FERNANDES, Flávio Pereira; SILVA, Gustavo Calce da; SILVA, Matheus Henrique de Oliveira; SANTOS, Silas Alves dos (210, 2023)
Este trabalho de conclusão de curso tem como proposta o desenvolvimento de um site personalizado para a ONG Acolhe Itaquá, visando ampliar seu alcance e aumentar sua efetividade. O site será uma plataforma online que possibilitará a divulgação das atividades da organização, a captação de doações e o cadastro de voluntários. Com o uso de linguagens de programação como PHP, HTML5, JavaScript e CSS3, e o banco de dados MySQL, o site será desenvolvido de forma a ser uma ferramenta eficiente e adaptada às necessidades da ONG. Além disso, será oferecido suporte técnico, consultoria e atualizações regulares para garantir seu pleno funcionamento. Através desse projeto, espera-se superar as dificuldades de visibilidade e captação de recursos enfrentadas pelas ONGs, melhorando a imagem da Acolhe Itaquá, atraindo doadores e engajando voluntários em prol da causa da organização. Com essa plataforma, a ONG terá a oportunidade de fortalecer sua atuação e contribuir de forma mais significativa para a comunidade.

This undergraduate thesis presents the development of a website for the Acolhe Itaquá NGO, aiming to expand its reach and effectiveness. The website will provide an online platform for promotion, donations, and volunteer registration, addressing the lack of visibility and fundraising challenges faced by NGOs. By utilizing languages such as PHP, HTML5, JavaScript, and CSS3, along with the MySQL database, the website will be an efficient and personalized tool, offering technical support, consulting, and regular updates. This project aims to improve the NGO's visibility, attract resources, and engage donors and volunteers, thus making a significant contribution to the organization's cause. The website will serve as a means to strengthen the NGO's presence, reaching a wider audience and allowing for better communication with potential donors and volunteers. Through this platform, the Acolhe Itaquá NGO will have the opportunity to showcase their activities, share success stories, and raise awareness about the issues they address. The website will also provide a secure and user-friendly interface for online donations, ensuring transparency and trust among donors. Additionally, the volunteer registration feature will streamline the process of recruiting and coordinating volunteers, maximizing the NGO's impact and efficiency.
Keywords: Web sites; Organização não governamental; Pessoas em situação de rua; Ação social; Sociedade civil; Informação e Comunicação